(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2015)
Econometrics expressed through a function focused on the management control of the production of goods and services is the focus of this research; particularly the use of indicators for purposes of supporting management, with the interest you receive this product on all kinds of public and private organizations, civil, military and religious. In the present study, the specific case of application is a company of the textile industry considered a feasible project. the solution or objective of turning the general variables in intermediate It arises and they eventually indicators or elementary variables that can be read or observed directly from the processes that are representative and can be obtained or measured in real time given the econometric forecasting processes by dynamic or autoregressive models; ie in full production processes, then correct the fly thereof, if they deviate from the goals pursued, before getting the final results. The final product being an econometric model that will increase the effectiveness, efficiency, effectiveness and competitiveness of the company.